"Human Nature" and the Biology of Everyday Life. Issue 2 (28th March 2019) - Wolf‐Meyer, Matthew
ABSTRACT: Anthropologists are well poised to contribute to an immanent theory of human physiological experiences that accounts for the broad social and environmental influences that shape individual and community experiences of health and disease. This article forwards a theory of "the biology of everyday life" as a means to conceptualize the interactions between institutional expectations of behavior, cultural norms, and biological plasticity. Drawing on a wide variety of research on human sleep, this article shows how the expression of sleep needs vary within and between societies and are shaped primarily not by innate biological drives but cultural norms embedded in the institutions that comprise the infrastructure of everyday life. Embracing perspectives from laboratory scientists, social theorists, and ethnographers, the biology of everyday life offers a way to conceptualize human nature not as a set of drives but a supple interaction of physiological plasticity, cultural expectations, and social organization. [ plasticity, social determinants of disease, epigenetics, sleep ] RESUMEN: Los antropólogos están bien posicionados para contribuir a una inmanente teoría de la fisiología humana que tiene en cuenta las amplias influencias sociales y ambientales que modelan las experiencias individuales y comunitarias de salud y enfermedad. Este artículo avanza una teoría de la biología de la vida cotidiana como un medio de conceptualizar las interacciones entre expectativas institucionales de comportamiento, normas culturales, y plasticidad biológica. Basado en una amplia variedad de investigaciones sobre el sueño humano, este artículo muestra cómo la expresión del sueño necesita variar dentro y entre sociedades y está modelado primariamente no por impulsos biológicos innatos sino por normas culturales embebidas en las instituciones que comprenden la infraestructura de la vida cotidiana. Acogiendo perspectivas de científicos de laboratorio, teóricos sociales, y etnógrafos, la biología de la cotidianeidad ofrece una manera de conceptualizar la naturaleza humana no como un juego de impulsos sino como una interacción flexible de plasticidad fisiológica, expectativas culturales, y organización social. [plasticidad, sueño, biología local, capitalismo industrial, biología como ideología]